2015
DOI: 10.3342/ceo.2015.8.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Extracapsular Spread of Metastatic Lymph Nodes in Papillary Thyroid Carcinoma

Abstract: ObjectivesThe extracapsular spread (ECS) of metastatic lymph nodes is associated with aggressive tumor behavior, and is regarded as a major risk factor for local recurrence in patients with head and neck squamous cell carcinoma. However, the significance of ECS of metastatic lymph nodes has not been well established in well-differentiated thyroid carcinoma. The purpose of this study was to examine this question.MethodsA retrospective review was performed of 335 patients with papillary thyroid carcinoma who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…Therefore, it's important to improve the thoroughness of CLND. Our results mirror the data from literature: Reoperative CLND has been shown to have rates of RLN injury 21% transiently and postoperative hypocalcemia with a large range of 0-24% [23][24][25][26][27][28][29][30] . However, the incidence of complications varies according to the skill and experience of the surgeon [7,31] .…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, it's important to improve the thoroughness of CLND. Our results mirror the data from literature: Reoperative CLND has been shown to have rates of RLN injury 21% transiently and postoperative hypocalcemia with a large range of 0-24% [23][24][25][26][27][28][29][30] . However, the incidence of complications varies according to the skill and experience of the surgeon [7,31] .…”
Section: Discussionsupporting
confidence: 88%
“…Yamashita et al first identified the prognostic importance of ENE as an indicator of distant metastasis in a case‐control study including 100 PTC patients . The close relationship between ENE and distant metastasis was also identified by Sugitani et al Thereafter, several studies have reported that ENE predicts high risk of recurrence and impaired cancer‐specific survival . Lango et al found that, after treatment, patients with ENE are less likely to have a complete biochemical response (a stimulated serum Tg of <1 ng/mL) and have an increased probability of tumor persistence after thyroidectomy, indicating eventual systemic disease progression .…”
Section: Discussionmentioning
confidence: 91%
“…10 The close relationship between ENE and distant metastasis was also identified by Sugitani et al 22 Thereafter, several studies have reported that ENE predicts high risk of recurrence and impaired cancer-specific survival. 7,9,11,14,23 They found that minimally invasive ETE was associated with a 13-fold increased incidence of ENE compared to tumors without ETE, and that tumors associated with ENE as well as ETE were larger, compared with those without either ETE or ENE (mean 2.3 vs 1.4 cm, P = 0.004). 23 However, small metastatic LNs have been shown to have ENE: 59% of the metastatic LNs with ENE were smaller than 1.5 cm, 26 the threshold size for recurrence previously reported by Ito et al 27 Our study also highlighted the close relationship between macroscopic ETE with ENE or macroscopic ENE, and showed that a higher number of metastatic LNs (>5) was also associated with ENE.…”
Section: Prediction Of Nodal Metastasis and Enementioning
confidence: 99%
See 2 more Smart Citations